Fundamentals of renal pathology - Fogo, Agnes B. (Springer Berlin Heidelberg, 2014)
Fundamentals of Renal Pathology is a compact and up-to-date resource on the basics of renal pathology that will be of particular value to residents and fellows in training in renal pathology, general pathology, and nephrology, but will also serve as a handy reference for the more experienced.   This second, revised and updated edition of the book offers an integrated approach based on contributions from established experts in the field. After considering normal renal anatomy and basic concepts and methods used in the assessment of renal biopsies, key diseases are discussed within the context of clinical presentations. The emphasis is on clinicopathological correlation and differential diagnosis. Topics discussed include glomerular diseases with nephrotic or nephritic syndrome presentations; systemic and vascular diseases affecting the kidney, including diseases affecting the renal transplant; tubulointerstitial diseases; and plasma cell dyscrasias and associated diseases. Well-chosen color illustrations and electron micrographs enhance and complement the text, and tables summarize the most up-to-date classifications and approaches for the various disease entities.